Analisis Dampak Praktik Ibadah Ramadan dan Interaksi Keluarga terhadap Ketahanan Keluarga Muslim di Kota Surakarta - Muhammad Amin Choiri Setiyanto; Nur Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
The holy month of Ramadan holds a significant position in the lives of Muslims as it entails not only a spiritual dimension but also social implications within family life. Various religious activities during Ramadan, such as having suhoor and iffat together, performing congregational prayers, and reciting the Qur'an within the family, have the potential to enhance interaction among family members and strengthen emotional bonds. In the context of urban societies with high levels of busyness, the momentum of Ramadan can serve as a means to strengthen togetherness and family resilience. However, empirical studies specifically examining the relationship between Ramadan religious practices, family interaction, and Muslim family resilience remain relatively limited. This study aims to analyze Ramadan religious practices in Muslim families, identify the level of family interaction during Ramadan, and analyze the influence of Ramadan religious practices and family interaction on the resilience of Muslim families in Surakarta. This study adopts a quantitative approach with a survey research design. The research population consists of Muslim families residing in Surakarta, with the sampling technique utilizing purposive sampling. Research data were gathered through questionnaires using a Likert scale distributed to approximately 100 Muslim family respondents. The obtained data were analyzed using validity tests, reliability tests, and multiple linear regression analysis to determine the influence of the independent variables on family resilience. The results of this study are expected to provide an empirical contribution to Islamic family law studies, particularly regarding the role of religious practices and family interaction in strengthening the resilience of Muslim families. Furthermore, this study is also expected to serve as a baseline for developing Muslim family development programs that utilize the momentum of Ramadan as a means to strengthen family relationships and resilience. Keywords: Ramadan, religious practices, family interaction, family resilience, Muslim family.